Assessment of Spatial Location and Air Transport Patterns of Minnesota’s Medical Device Industry Cluster - Munnich, Lee; Fried, Travis; Cho, Joanne; Horan, Thomas (Journal of Strategic Innovation and Sustainability, 2021)
Minnesota’s medical device industry cluster is not only one of the biggest driving economic forces in the state, but also a global leader in the development and distribution of medical devices. The study assessed the medical device industry’s spatial development and air transport implications, both in terms of industry cluster location and flow of products. The spatial analysis showed that most medical device companies are located within the seven-county Twin-Cities region, but that industries linked to the medical device industry cluster are much more dispersed throughout the state. Regarding products created, the supply chain of medical devices is highly dependent on Minneapolis-St Paul Airport (MSP), which plays a key role in their delivery of medical devices. Air Cargo analysis reveals the high value of medical devices. exports to various locations and raises issues about the future role of air cargo through MSP to the economic prosperity of the industry cluster.